Enhancing Fiqh al-Ibadah Learning Through Humanistic E-Modules at Pesantren Muhammad Natsir - Jarudin Jarudin; Nurul Mu’tamim; Sefni Novita Sari; Wira Solina; Dina Amaluis (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This study investigates the integration of e-modules in teaching fiqh al-ibadah within the framework of humanistic Islamic education at Pesantren Muhammad Natsir. The research examines the effectiveness of digital modules, patterns of teacher student interaction, and the incorporation of humanistic values in the learning process. Using a qualitative case study approach, the study involved two fiqh teachers and three students as participants. Although limited in number, the participants were sufficient for in-depth exploration within this case study context. Data were collected through participatory observation, in-depth interviews, and document analysis. The findings indicate that the use of e-modules improves students’ understanding of worship procedures, particularly in topics such as ablution (wuḍū’), dry ablution (tayammum), and prayer movements, through visual explanations and structured learning steps. Students were able to review the learning material independently before classroom practice, which increased their participation during discussions and practical sessions. The reflection sections included in the e-modules also encouraged students to evaluate their daily worship practices and better understand the ethical and spiritual meaning behind ritual activities. From the teachers’ perspective, e-modules reduce repetitive explanations and allow more instructional time to be devoted to guiding practical worship exercises. This study contributes to the discussion on technology integration in Islamic education by proposing a humanistic and context-sensitive model of fiqh learning in pesantren. The findings demonstrate that digital learning media, when designed pedagogically, can strengthen students’ understanding of worship practices while maintaining the spiritual values that characterize pesantren education.